Validasi Metode Deteksi Shigella dalam Tablet Hisap Obat Kuasi - Herawati, Desty; Aprianto, Eko; Cahyaningsih, Eni; Miftahurrohmah, Nur (Badan Pengawas Obat dan Makanan, 2024)
Lozenges, a quasi-drug used to relieve sore throats, must meet the safety and quality requirements according to Indonesian FDA Regulation No. 7 of 2023 concerning the criteria and procedures for quasi-drug registration, which stipulates that oral preparations of quasi-drugs must be free from Shigella spp—microbial contamination. Contamination by Shigella bacteria can cause diseases such as shigellosis, characterized by symptoms such as diarrhoea, vomiting, and fever. This study aims to validate the Shigella spp—detection method in quasi-drug lozenges using the WHO (Quality Control Methods for Herbal Materials) reference method. Validation was carried out to ensure that this method can be used for routine analysis in the Indonesian FDA laboratory. The guidelines used to validate the microbiological method are the Singapore Accreditation Council (SAC) Guidance Notes C&B AND ENV 002 of 2019 and refer to pharmacopoeias. The study results showed that the WHO (Quality Control Methods for Herbal Materials) method in detecting Shigella sp. has a sensitivity and specificity of 100%, with false positive and false negative rates of 0% each. The detection limit obtained was 3 cfu/g, which meets the requirements (below 10 cfu/g). The method suitability test (optimization) showed that the initial solvent used for sample homogenization in Shigella detection was sufficient using Tryptone Soya Broth (1:10) without additional neutralization or modification procedures at the sample homogenization stage. Based on these results, the Shigella spp. The WHO reference (Quality Control Methods for Herbal Materials) detection method is accurate. It can be applied for routine microbial contamination testing analysis in the Food and Drug Supervisory Agency laboratories.